Proposal for an equivalent frame model for the analysis of multi-storey monolithic CLT shearwalls. (15th October 2021) - Casagrande, Daniele; Doudak, Ghasan; Vettori, Matteo; Fanti, Riccardo
Highlights: A simple yet robust model for the analysis of multi-storey CLT shearwalls is presented. The mechanical interaction between wall segments and lintels is studied. Pushover analyses are conducted on the proposed equivalent frame model. The proposed EFM is compared with published test results on CLT shearwalls. Abstract: The paper presents a simple yet robust frame model to be used as an alternative to continuous 2D or 3D finite element models for the purpose of analyzing multi-storey cross-laminated timber (CLT) shearwalls with openings when subjected to lateral loads. The proposed model is applicable to monolithic CLT walls and takes into account the mechanical interaction between wall segments and lintel/parapet elements as well as the non-linear behaviour of the mechanical anchors, while the contribution of the vertical load is omitted. Pushover numerical analyses were conducted on the proposed equivalent frame model (EFM) and 2-D finite element model, and the results showed good agreement between the two models along the entire force-displacement curves. The failure conditions were found to be consistent in all cases, and the distribution of the internal forces were found to be reasonable. The proposed EFM was also compared with published test results on CLT shearwalls and the fit was deemed reasonable, with a slight tendency to underestimating the ultimate capacity of the shearwalls.